MsLHY is an active regulator of cold resistance in alfalfa (Medicago sativa L.) - Li, Jikai; Chai, Lu; Yang, Mei; Zhang, Hailing; Shang, Chen; Liu, Yuxuan; Qian, Kailin; Sun, Jiuding; Han, Weibo; Zhang, Pan (Frontiers in Plant Science, 2025)
Low-temperature stress is a major environmental factor that limits the yield, quality, and geographical distribution of forage crops and restricts the development of the forage industry. As a core component of plant circadian clocks, Late Elongated Hypocotyl (LHY) plays a crucial role in regulating plant rhythms and responses to abiotic stress. However, the molecular mechanism by which LHY regulates the cold tolerance of alfalfa has not been reported. In this study, MsLHY, which is 2,235 bp in length and encodes 744 amino acids, was isolated from alfalfa. MsLHY was highly expressed in roots and stems and was significantly induced by low temperature. Transgenic MsLHY-overexpressing (OE) and RNAi alfalfa plants were obtained via Agrobacterium-mediated transformation. Under low-temperature stress, OE plants presented reduced reactive oxygen species accumulation and more osmotic regulatory substances, as well as greater antioxidant enzyme activity, to combat cold stress. Conversely, the RNAi plants presented trends opposite those of the OE plants. Furthermore, under cold stress, the overexpression of MsLHY upregulated the expression of the cold-responsive genes MsICE1, MsCBF1, MsCOR15A, and MsCML10, as well as the expression of the antioxidant-synthesizing genes MsSOD1 and MsCAT1, thereby increasing the cold tolerance of transgenic alfalfa. These results suggest that MsLHY plays an important role in increasing the cold tolerance of alfalfa.